2007
DOI: 10.1248/bpb.30.2191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Licorice Extract against Tumor Growth and Cisplatin-Induced Toxicity in a Mouse Xenograft Model of Colon Cancer

Abstract: Cisplatin (cis-diamminedichloroplatinum II) is a platinum coordinated complex that is widely used as an antineoplastic agent for the treatment of many solid tumors, including cancers of the ovary, testis, lung, bladder, head and neck, cervix and endometrium.1) Despite its excellent anticancer activity, the clinical use of cisplatin is often limited by its undesirable side effects, such as severe nephrotoxicity and hepatotoxicity. 2,3) Although the precise mechanism for this cisplatin-induced toxicity is not we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 31 publications
2
61
0
1
Order By: Relevance
“…Previous studies on the development of chemotherapeutic agents have been focused on inducing cancer-specific cell death through the modulation of apoptosis, or programmed cell death. Furthermore, to overcome the side effects of current chemotherapeutic agents, studies have focused on the anti-cancer activity of natural compounds purified from herbal plants (7,(11)(12)(13)(14)(15). As a result of these studies, the US Food and Drug Administration approved the clinical use of a medicinal herbal plant-derived natural compound with anti-cancer activity for cancer therapy (16).…”
Section: Licochalcone-e Induces Caspase-dependent Death Of Human Pharmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the development of chemotherapeutic agents have been focused on inducing cancer-specific cell death through the modulation of apoptosis, or programmed cell death. Furthermore, to overcome the side effects of current chemotherapeutic agents, studies have focused on the anti-cancer activity of natural compounds purified from herbal plants (7,(11)(12)(13)(14)(15). As a result of these studies, the US Food and Drug Administration approved the clinical use of a medicinal herbal plant-derived natural compound with anti-cancer activity for cancer therapy (16).…”
Section: Licochalcone-e Induces Caspase-dependent Death Of Human Pharmentioning
confidence: 99%
“…Licorice has been used as a medication for stomach ulcers, bronchitis and sore throats (7,17). Furthermore, the anticancer activity of licorice has been reported in breast (18,19), oral (11), colon (12) and prostate cancer (13). Licorice inhibits metastasis (18), has anti-proliferative properties (19), increases apoptosis and may cause cell cycle arrest (14).…”
Section: Licochalcone-e Induces Caspase-dependent Death Of Human Pharmentioning
confidence: 99%
“…Recent studies have reported that licorice roots contain multiple bioactive components such as saponins, flavonoids, and coumarins [13][14][15]. Furthermore, licorice has been shown to have anticancer effects in various types of cancer such as colon [16], lung [17,18], breast [19,20], prostate [21], and oral cancers [11] through metastatic inhibition [19], anti-proliferative properties [20], increased apoptosis [11,22], and cell cycle arrest [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been an upsurge of interest in the therapeutic potentials of medicinal plants as antioxidants in alleviating oxidative stress-induced pathologies (Lans et al, 2007;Lee et al, 2007). Several studies revealed that medicinal plants contain diverse classes of bioactive compounds such as polyphenols, tocopherols, alkaloids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that medicinal plants contain diverse classes of bioactive compounds such as polyphenols, tocopherols, alkaloids, etc. (Gordana et al, 2004;Lee et al, 2007). Among them, flavonoids are particularly attractive as they are known to exhibit various pharmacological properties such as vasoprotection, anti-carcinogenic, anti-microbial, antiinflammatory and anti-proliferative effects (Gordana et al, 2004).…”
Section: Introductionmentioning
confidence: 99%